Marketing Strategy of Teaching Hospital: Challenges For Teaching Hospitals in Indonesia - Ardiansyah Ardiansyah; Amal Chalik Sjaaf (Syntax Literate, 2023)
The increasing demands of the community for quality and affordable health services make hospitals have to always try to survive amid increasing competition. This article is a systematic review where data is taken from online databases such as ProQuest, Wiley Online, JStore, ScienceDirect, Embase, Scopus, and local journals (Garuda Portal, Jurnal Promkes) using the keywords "Strategy", and "Hospital Marketing", "Marketing". The search engine obtained 6234 international journals and 6 local journals. Then again sorting by year (starting from 2012 and above), duplication, type of article (journal, not systematic review), and full article only, then the final result is 7 titles. The result of this literature review article may provide experiences for directing future investigations regarding the marketing strategy of a teaching hospital. Thus, the findings of this article could help governments, universities, health providers, and academia to concentrate their efforts and policies on the development of the current teaching hospital, especially using marketing tools. Directions for improving the healthcare systems should mainly focus on reducing diseases, disabilities, and mortality among the population; improving the quality and accessibility of healthcare; and developing a competitive market of innovative medical services. The creation of an effective healthcare system could lead to improving the quality of life. Hospital marketing is an important element in introducing the hospital to the wider community. It is necessary to combine and coordinate related elements so that marketing programs can be carried out as effectively as possible.